Students’ Motivation In Speaking English Using Tiktok - Faishol Hadi; Fachrizal Dadang (STKIP AL HIKMAH SURABAYA, 2025)
At present, technology is rapidly advancing, which is undoubtedly a positive development that we should harness. Social media is one of the outcomes of this technological progress. Nowadays, the use of social media goes beyond being merely a means of communication; it has been utilized in various sectors such as the economy, religion, tourism, and education. One of the relatively recent additions to the realm of social media is TikTok. This research aims to explore how students are motivated in learning speaking skills using TikTok. A qualitative descriptive approach was chosen for this study. A motivation questionnaire was employed to identify the motivational aspects that emerge, as well as the TikTok features that contribute to speaking skill acquisition. Additionally, semi-structured interviews were conducted to gain deeper insights. This research involved a class at SMA N Jatirogo. The findings of this study indicate that TikTok has a positive impact on enhancing student motivation. Motivation is evident in various aspects, such as enjoyment, challenges, increased curiosity, and more. However, there are still some aspects that need further optimization and improvement in using TikTok for speaking skill development, including monitoring TikTok usage and certain social aspects that may not be as impactful as desired. This research can be valuable for prospective teachers and educators who intend to use TikTok as a tool for teaching the English language